2002
DOI: 10.1046/j.1523-1747.2002.19615.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Microphthalmia-associated Transcription Factor Gene Expression Alters Skin Pigmentation

Abstract: The microphthalmia-associated transcription factor is implicated in melanocyte development and in the regulation of melanogenesis. Microphthalmia-associated transcription factor is thought to bind to the M-box promoter elements of tyrosinase, tyrosinase-related protein-1 and dopachrome tautomerase/tyrosinase-related protein-2 and transactivate these genes, resulting in increased pigmentation. Using a luciferase reporter construct driven by the microphthalmia-associated transcription factor promoter, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 66 publications
2
80
0
3
Order By: Relevance
“…5) Melanin is synthesized in epidermal melanocytes, and then is transferred into epidermal keratinocytes via the melanocytes' dendrites. 6) Melanogenesis is the process by which melanin is produced (and subsequently distributed) by melanocytes within the skin and hair follicles. 7) This process results in the synthesis of melanin pigments, which plays a protective role against skin photocarsinogenesis.…”
mentioning
confidence: 99%
“…5) Melanin is synthesized in epidermal melanocytes, and then is transferred into epidermal keratinocytes via the melanocytes' dendrites. 6) Melanogenesis is the process by which melanin is produced (and subsequently distributed) by melanocytes within the skin and hair follicles. 7) This process results in the synthesis of melanin pigments, which plays a protective role against skin photocarsinogenesis.…”
mentioning
confidence: 99%
“…The microphthalmia-associated transcription factor is implicated in melanocyte development and also upregulates melanogenesis via transactivation of tyrosinase gene expression. Lin et al (2002) showed that LA reduced the microphthalmia-associated transcription factor and tyrosinase promoter activities, resulting in depigmentation. Attention should be focused on the regulative mechanisms of LA, not only a reduction of intracellular tyrosinase expression but also direct tyrosinase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Dihydrolipoic acid is capable of enhancing antioxidant potency by regenerating L-ascorbic acid vitamin E (Kagan et al, 1992), and reportedly impacts both the regulation of tyrosinase gene expression and direct inhibition of tyrosinase (Lin et al, 2002). Moreover, dihydrolipoic acid is considered to have superior inhibitory activity in melanin biosynthesis when compared to parent LA (Tsuji-Naito et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosinase activity was determined according to the method of Lin et al (24). B16 and A375 cells were seeded and treated as described above.…”
Section: Methodsmentioning
confidence: 99%